On the Adjacent Cycle Derangements. (2nd December 2012) - de Francesco Albasini, Luisa; Zagaglia Salvi, Norma
Abstract : A derangement, that is, a permutation without fixed points, of a finite set is said to be an adjacent cycle when all its cycles are formed by a consecutive set of integers. In this paper we determine enumerative properties of these permutations using analytical and bijective proofs. Moreover a combinatorial interpretation in terms of linear species is provided. Finally we define and investigate the case of the adjacent cycle derangements of a multiset.